Somatic Symptoms Among US Adolescent Females: Associations with Sexual and Physical Violence Exposure - Halpern, Carolyn Tucker (2013)
OBJECTIVE: To examine the association between physical and sexual violence exposure and somatic symptoms among female adolescents. METHODS: We studied a nationally representative sample of 8,531 females, aged 11–21 years, who participated in the 1994–95 Wave I of the National Longitudinal Study of Adolescent Health (Add Health). Female adolescents were asked how often they had experienced 16 specific somatic symptoms during the past 12 months. Two summary categorical measures were constructed based on tertiles of the distributions for the entire female sample: a) total number of different types of symptoms experienced, and b) number of frequent (once a week or more often) different symptoms experienced. Groups were mutually exclusive. We examined associations between adolescents’ violence exposure and somatic symptoms using multinomial logistic regression analyses. RESULTS: About 5% of adolescent females reported both sexual and non-sexual violence, 3% reported sexual violence only, 36% reported non-sexual violence only, and 57% reported no violence. Adolescents who experienced both sexual and non-sexual violence were the most likely to report many different symptoms and to experience very frequent or chronic symptoms. Likelihood of high symptomotology was next highest among adolescents who experienced sexual violence only, followed by females who experienced non-sexual violence only. CONCLUSIONS: Findings support an exposure-response association between violence exposure and somatic symptoms, suggesting that symptoms can be markers of victimization. Treating symptoms alone, without addressing the potential violence experienced, may not adequately improve adolescents’ somatic complaints and well-being.